PERAN KEBIJAKAN RASKIN TERHADAP POLA PENGELUARAN RUMAH TANGGA PENERIMA RASKIN DI KOTA BANDAR LAMPUNG - Eka Prianti; Bustanul Arifin; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
This research aims to analyze the role of raskin (poor rice) policy toward household expenditurepattern and household response toward the policy of Raskin food card replacement in Bandar Lampung City. The numbers of respondents in this research were 137 respondents that were determined by accidental sampling method. The data was analyzed by descriptive analysis, different test and cross tabulation. The results showed that there was reduction of household expenditure burden for grainafter receiving Raskin subsidy that was equal to 4.69 percent. There was consumption escalation of vegetable protein sources (1%), animal protein sources (2.22%) and fruit (1%) of households in Bandar Lampung City after receiving Raskin subsidy. Household non-food expenditures, such as household needs, clothing, housing and telecommunications were increased by less than 1 percent. The factors that affected household responses in Bandar Lampung City to food card policy was the number of dependents and income, while the age and education of respondents did not affect the response of households in Bandar Lampung to Raskin card policy.Key words: expenditure pattern, food card, raskin